Is the 'Linkage Principle' Valid? Evidence from the Field. (June 2014) - Cho, Sung‐Jin; Paarsch, Harry J.; Rust, John
<x xml:space="preserve">Abstract</x> We present field evidence concerning experienced bidders that supports the linkage principle—specifically, the prediction that in affiliated‐values auction environments the expected revenues generated at open‐outcry, ascending‐bid auctions are higher than those under auction formats that reveal less information to participants. Using field data from a large seller of automobiles who experimented with different selling formats, we have found that average revenues were significantly higher under an English auction than under a dynamic Internet auction format that revealed less information to bidders.